Rakoff test, diagnostic adjunct in the chronological pregnancy - Ludmir Grimberg, Abraham (2015)
Based in the study of 122 women in the past three months of pregnancy the authors compare the papanicolaou's and Rakoff's procedures to stain vaginal smears as methods to evaluate the progress of pregnancy. The rapid method of Rakoff renders as good results as those obtained with Papanicolaou's stain.